MAPEAMENTO TERMINOLÓGICO: UMA EXPERIÊNCIA BASEADA NAS DISSERTAÇÕES DE UM MESTRADO PROFISSIONAL - Dias, Elizabeth Abib Vasconcelos (2012)
The revolution produced by the electronics and computing, coupled with the explosion of documents, from the second half of the twentieth century, organizing and representing information have become fundamental processes in the dissemination and production of scientific and technological knowledge in all fields. The present work aims to build a Terminology mapping and a Database of keywords to support information retrieval and management of knowledge generated within a Master's degree professional. For achieve this goal as part of the method was performed the technical processing of a list of keywords obtained from the papers prepared in the Masters Program in Professional Management Systems (MSG), the Universidade Federal Fluminense (UFF), considering the dissertations completed in the years 2007 , 2008 and 2009 a total of 126 dissertations. The main steps of the methodology were performed: a literature review, sample definition, reading the metadata of dissertations, analysis, approval and standardization of the set of keywords; validation of definitions, analysis of relationships between terms and definition of models knowledge representation. It were obtained quantitative and qualitative informations of these procedures, pointing to constructive results, made possible the development of the Bank Standardized Keywords and Ontology, which when made available to users in the course page might, interactively, to support the academic work the course.